Особливості розпізнавання тексту та символів - Якимаха, М. Є. (ХНУРЕ, 2021)
In today's world, intelligent object recognition technology as well as text recognition are in high demand. Prospects for the development of intelligent text recognition are very great. Thanks to translators that use real-time text recognition through the camera, the language barrier for people who do not know a foreign language is erased.
Keywords: розпізнавання тексту; символ